The Effect of Water of Crystallization on Isomerization of Liposome using Sodium Sulfide Nonahydrate - Mohammed Fanokh Al-Owaidi (Journal of Global Pharma Technology, 2016)
The endogenous sulfide radicals (HS·/ S-·) play an important role in the biological system. They have cyto-protective antioxidant and pro-oxidants adverse effect. Sulfide radicals can produce isomerization of fatty acid physiologically and pathologically. In terms of biomimetic model using liposome, these radicals can produce trans fatty acid. The production of thiyl radical via photolysis was reported using sodium sulfide nonahydrate (Na2S.9H2O) 'H2S donor' in a phosphate buffer (PH=5.0). The efficacy of Na2S.9H2O to produce thiyl radical (HS·/ S-·) was evaluated by GC using POPC vesicle in phosphate buffer (PH=5). It has been noticed that the maximum isomerization rate was up to 35% of trans oleic acid after (30 minutes). The declining in the percent of isomerization on what was previously reported is attributing to the low diffused concentration of the H2S, that is due to the crystallization nature of sodium sulfide nonahydrate as well as the low solubility profile of hydrated sodium sulfide. Furthermore, it also refers to the high affinity of thiyl radicals to make weak isomerizing species such as sulfide dimer (HSSH) and polysulfide (Sn2-) in a heat releasing process. Polysulfides themselves have the ability to scavenge the thiyl radical (HS·/ S-·) and then inhibit the isomerization process (Scheme 1).Keywords: Liposomes, Sodium sulfide nonahydrate, Water of crystallization, Trans oleic acid, Trans fatty acid (TFA), Omega-9, POPC vesicle, Polysulfide, Thiyl radical.